OsCNGC13 promotes seed-setting rate by facilitating pollen tube growth in stylar tissues. - Yang Xu; Jie Yang; Yihua Wang; Jiachang Wang; Yang Yu; Yu Long; Yunlong Wang; Huan Zhang; Yulong Ren; Jun Chen; Ying Wang; Xin Zhang; et al. (PLoS Genetics, 2017)
Seed-setting rate is a critical determinant of grain yield in rice (Oryza sativa L.). Rapid and healthy pollen tube growth in the style is required for high seed-setting rate. The molecular mechanisms governing this process remain largely unknown. In this study, we isolate a dominant low seed-setting rate rice mutant, sss1-D. Cellular examination results show that pollen tube growth is blocked in about half of the mutant styles. Molecular cloning and functional assays reveals that SSS1-D encodes OsCNGC13, a member of the cyclic nucleotide-gated channel family. OsCNGC13 is preferentially expressed in the pistils and its expression is dramatically reduced in the heterozygous plant, suggesting a haploinsufficiency nature for the dominant mutant phenotype. We show that OsCNGC13 is permeable to Ca2+. Consistent with this, accumulation of cytoplasmic calcium concentration ([Ca2+]cyt) is defective in the sss1-D mutant style after pollination. Further, the sss1-D mutant has altered extracellular matrix (ECM) components and delayed cell death in the style transmission tract (STT). Based on these results, we propose that OsCNGC13 acts as a novel maternal sporophytic factor required for stylar [Ca2+]cyt accumulation, ECM components modification and STT cell death, thus facilitating the penetration of pollen tube in the style for successful double fertilization and seed-setting in rice.